Trade and transfer of environmentally sound technology in ASEAN: Mapping priorities to economic treaty negotiations - HSU, Locknie (Institutional Knowledge at Singapore Management University, 2022)
The 10 members of the Association of Southeast Asian Nations (“ASEAN”) share common objectives in economic, sociocultural and political-security integration. Addressing environmental concerns is animportant consideration which traverses different areas of integration policymaking. ASEAN has, in recent years, emphasised the importance of environmental considerations, including environmentally sound technologies (“ESTs”) which may contribute to its climate change mitigation and adaptation efforts, in its law and policymaking. This article discusses the nexus between ASEAN’s needs for the transfer of ESTs and the group’s economic treaty negotiations. Through a “mapping” of such needs to free trade agreementareas, it aims to provide a pathway to new considerations and opportunities to facilitate the transfer of ESTs, particularly when ASEAN conducts reviews and negotiations of such agreements.